2017
DOI: 10.1016/j.breast.2016.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Overdiagnosis in breast imaging

Abstract: The main harm of overdiagnosis is overtreatment. However a form of overdiagnosis also occurs when foci of cancer are found by imaging in addition to the symptomatic lesion when this leads to additional treatment which does not benefit the patient. Even if overtreatment is avoided, knowledge of the diagnosis can still cause psychological harm.Overdiagnosis is an inevitable effect of mammographic screening as the benefit comes from diagnosing breast cancer prior to clinical detectability. Estimates of the rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…This implies that using this AI system in screening is likely to maintain or increase the detection rate of in situ cancers, hence possibly adding to overdiagnosis [27]. On the other hand, of the cancers that were missed by AI, three out of seven were small, low-grade invasive tubular cancers, which in the light of overdiagnosis might not necessarily be a drawback [28]. Studies with other AI vendors have shown varying results; the sensitivity for calcifications can increase with the assistance of AI [10] or that AI seems to be more sensitive to invasive than in situ cancers [8].…”
Section: Discussionmentioning
confidence: 99%
“…This implies that using this AI system in screening is likely to maintain or increase the detection rate of in situ cancers, hence possibly adding to overdiagnosis [27]. On the other hand, of the cancers that were missed by AI, three out of seven were small, low-grade invasive tubular cancers, which in the light of overdiagnosis might not necessarily be a drawback [28]. Studies with other AI vendors have shown varying results; the sensitivity for calcifications can increase with the assistance of AI [10] or that AI seems to be more sensitive to invasive than in situ cancers [8].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that TC has limited impact on outcome ( 3 , 8 , 18 , 33 36 ), several groups hypothesized that its detection could represent an example of overdiagnosis ( 37 ). However, Aulmann et al ( 38 ) provided the molecular evidence for a direct clonal relationship of flat epithelial atypia and low-grade ductal carcinoma in situ with TC, indicating their precursor role.…”
Section: Discussionmentioning
confidence: 99%
“…The cumulative probabilities of false positive findings from screening mammography over 10 years of annual screening in the United States is as high as 61%, and can be up to 16% for a woman’s first mammogram 2 , 9 12 . The data range widely for estimated rates of breast cancer overdiagnosis, from 5% to 50%; contributing to this variability is the lack of consensus on the definition of overdiagnosis and how to measure it 13 . In addition to physical harms from unnecessary testing, procedures, or treatment, women can also experience significant psychological distress with false positive results.…”
Section: Screening Mammography In Average-risk Women: a Brief Summarymentioning
confidence: 99%